Blurred Boundaries and Hybrids in Revelation - Newton, Jon K. (Australian biblical review, 2023)
A key feature of the Book of Revelation is its "black and white" binary thinking, its hard boundaries. But the idea of such strict boundaries in Revelation has been challenged by writers like Leonard Thompson. Some boundaries are clearly soft or porous, so that people can pass from one state to another. Other boundaries are blurred or ambiguous, especially in relation to identity and ontology. For example, the identity of angels is quite ambiguous: are the "angels" of the churches really angels? Is the super-angel of Revelation 10 really an angel or perhaps a Christophany? Are the "seven spirits of God" angels or the Holy Spirit? Angels seem to function as a kind of hybrid in these examples. There are also explicitly hybrid creatures: the four "living beings" in heaven (Rev 4:6-8), the hybrid locustscorpions of Rev 9:3-11, the two beasts of Revelation 13. In this article I explore the function of such hybrid and ambiguous creatures in the Hebrew Bible, Jewish apocalypses, Dead Sea Scrolls and ancient Near East and Greco-Roman culture, including astrology, to shed light on John's intentions here. I argue that the hybrid and ambiguous entities of Revelation actually serve the "warfare worldview" of Revelation.